UJI SENSITIVITAS SIPROFLOKSASIN DAN TETRASIKLIN TERHADAP Staphylococcus aureus PADA PEROKOK - TITIN NURJANAH; ANCE ROSLINA; IHAM HARIAJI; ANNISA ANNISA (JURNAL ILMIAH KOHESI, 2023)
Exposure to smoke in cigarettes can increase the risk of respiratory tract infection due to Staphylococcus aureus. The treatment uses broad spectrum antibiotics including Fluoroquinolones. This study aims to determine the sensitivity test of Ciprofloxacin and Tetracycline to Staphylococcus aureus in smokers. This study uses analytic observational design and fulfills the inclusion and exclusion criteria by purposive sampling. The number of samples are 25 smoker’s throat swab samples that were Gram stained, culture in MacConkey Agar and MSA, as well as Ciprofloxacin and Tetracycline antibiotic test. Data was processed by descriptive analysis. Sensitivity test Ciprofloxacin was obtained sensitive 36%, Intermediate 36%, Resistance 28% and Tetracycline are there sensitive 68%, Intermediate 12%, Resistance 20%. There is sensitivity to Ciprofloxacin and Tetracycline against Staphylococcus aureus in smokers.